Aflibercept for the therapy of retinal diseases. A review of clinical studies - T. D. Okhotsimskaya; O. V. Zaitseva (Российский офтальмологический журнал)
Aflibercept is a hybrid protein-imitation of VEGF receptor with a prolonged activity. The review describes the structural properties of the Aflibercept molecule, the impact of the medication on the pathogenesis of retinal diseases, and the results of clinical studies into the safety and effectiveness of Aflibercept in the therapy of age related macular degeneration (VIEW1, VIEW2), diabetic macular oedema (VISTA, VIVID), macular oedema caused by the occlusion of the central retinal vein (GALILEO, COPERNICUS) or its branches (VIBRANT), and myopic choroidal neovascularization (MYRROR) Russian ophthalmological journal. 2017; 10 (2): 103-11. (in Russian). doi: 10.21516/2072-0076-2017-10-2-103-111.